The basics of Christian belief: Bible, theology, and life's big questions - Strahan, Joshua Marshall (Baker Academic, a division of Baker Publishing Group, 2020)
"This accessible and engaging book helps readers understand the essentials of the Christian faith and the impact they have on life, worldview, and witness"--